2022
DOI: 10.1523/eneuro.0107-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Visual System Hyperexcitability and Compromised V1 Receptive Field Properties in Early-Stage Retinitis Pigmentosa in Mice

Abstract: Inherited retinal degenerative diseases are a prominent cause of blindness. Although mutations causing death of photoreceptors are mostly known, the pathophysiology downstream in the inner retina and along the visual pathway is incompletely characterized in the earliest disease stages. Here, we investigated retinal, midbrain and cortical visual function using electroretinography (ERG), the optomotor response (OMR), visual evoked potentials (VEPs), respectively, and single unit electrophysiology at the primary … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 76 publications
1
2
0
Order By: Relevance
“…Similar to our observations after the onset of retinal degeneration, different murine models of retinitis pigmentosa showed heightened excitability in V1 (Wang et al, 2016 ; Chen et al, 2020 ; Leinonen et al, 2022 ), accompanied by impairments in neurophysiological properties such as visual stimulus direction selectivity (Chen et al, 2016 ; Leinonen et al, 2022 ). In addition, human retinitis pigmentosa patients report visual impairments beyond loss of vision, which might be attributed to aberrant retinal activity (Stasheff, 2018 ).…”
Section: Discussionsupporting
confidence: 88%
“…Similar to our observations after the onset of retinal degeneration, different murine models of retinitis pigmentosa showed heightened excitability in V1 (Wang et al, 2016 ; Chen et al, 2020 ; Leinonen et al, 2022 ), accompanied by impairments in neurophysiological properties such as visual stimulus direction selectivity (Chen et al, 2016 ; Leinonen et al, 2022 ). In addition, human retinitis pigmentosa patients report visual impairments beyond loss of vision, which might be attributed to aberrant retinal activity (Stasheff, 2018 ).…”
Section: Discussionsupporting
confidence: 88%
“…Literature on the degenerate retina's functional capacity is limited, mostly focusing on changes in photoreceptor-driven responses at earlier stages of degeneration. Although contrast sensitivity seems well preserved in those studies, 39,40 some loss of function has been found, including attenuated response amplitude, longer onset latency, smaller receptive fields, and the loss of inhibitory/OFF responses in rd1 mice. 40 Our data are consistent with the view that these features are more a consequence of photoreceptor depletion/dysfunction than network reorganization.…”
Section: Discussionmentioning
confidence: 82%
“…There is limited literature on the functional capacity of the degenerate retina, which has mostly focused on changes to photoreceptor-driven vision in early stages of retinal degeneration. While contrast sensitivity seems to be well preserved (Leinonen et al, 2022;Procyk et al, 2019), there is evidence of loss-of-function in some of the visual properties we tested, including attenuated response amplitude, onset latency, smaller receptive fields and an absence of sustained inhibitory/OFF responses (Procyk et al, 2019). Given that we have found the rd1 retina retains the capacity to support these characteristics during optogenetic interrogation of bipolar cells, it is likely these findings are due to changes in photoreceptors or the first retinal synapse rather than changes later in the visual pathway.…”
Section: Discussionmentioning
confidence: 95%